2000
DOI: 10.2337/diabetes.49.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Increased mRNA levels of Mn-SOD and catalase in embryos of diabetic rats from a malformation-resistant strain.

Abstract: Previous studies have suggested that reactive oxygen species (ROS) are mediators in the teratogenic process of diabetic pregnancy. In an animal model for diabetic p r e g n a n c y, offspring of the H rat strain show minor dysmorphogenesis when the mother is diabetic, whereas the offspring of diabetic rats of a sister strain, U, display major morphologic malformations. Earlier studies have shown that embryonic catalase activity is higher in the H than in the U strain, and maternal diabetes increases this diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
41
0
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 42 publications
5
41
0
2
Order By: Relevance
“…Provided that there is an increased cell death also in the cells migrating from the crest, it can be assumed that the delay in cranial nerve ganglion development is due to enhanced cell death rather than merely a delayed neural crest-cell migration. Moreover, the malformations induced by diabetic pregnancy are often attributed to free oxygen radicals [28,29,30,31] and the neural crest cells are reported to have low activity of the radical scavenging enzyme superoxide dismutase [32]. The combination of increased oxidative stress and a cell type with low antioxidant capacity could therefore cause the malformations present in neural crest-derived organs in diabetic pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Provided that there is an increased cell death also in the cells migrating from the crest, it can be assumed that the delay in cranial nerve ganglion development is due to enhanced cell death rather than merely a delayed neural crest-cell migration. Moreover, the malformations induced by diabetic pregnancy are often attributed to free oxygen radicals [28,29,30,31] and the neural crest cells are reported to have low activity of the radical scavenging enzyme superoxide dismutase [32]. The combination of increased oxidative stress and a cell type with low antioxidant capacity could therefore cause the malformations present in neural crest-derived organs in diabetic pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Cederberg et al (2000) found that rat embryos of a strain resistant to maternal diabetesinduced malformations had higher constitutive and inducible levels of mRNAs for catalase and superoxide dismutase. Studies of homocysteine also found stronger associations between maternal hyperhomocysteinemia and NTDs among fetal groups carrying the C3 T MTHFR enzyme mutation (Wenstrom et al, 2000).…”
Section: Fetal Factors In Oxidant Stressmentioning
confidence: 99%
“…Eriksson et al also described a high rate of congenital malformations in a substrain of Sprague-Dawley rat, denoted U strain, that was developed spontaneously out of the H strain and did not develop congenital anomalies [7]. The catalase activity and levels of catalase and Mn-SOD mRNA were decreased in the U embryos when compared with that of the H embryos, reducing further when the mother was diabetic [5,11,22]. The authors suggested that the impaired expression of scavenging enzymes in response to reactive oxygen species excess might be genetically determined.…”
mentioning
confidence: 99%
“…It has, however, been suggested that both intrauterine (maternal) environment as well as genetic background may be important [1][2][3][4][5][6][7] in the teratogenic process. As of today, the literature describes 3 main pathways by which diabetes may affect the normal development of the embryos: disturbed inositol uptake, yielding lowered intracellular inositol concentration [8]; diminished flow in the arachidonic acid-prostaglandin pathway, yielding decreased PGE2 concentration [9]; and excess amount of reactive oxygen species, resulting in decreased amount of low-molecular-weight antioxidants, such as vitamin C, uric acid, glutathione, and vitamin E [5,6,10,11]. The reactive oxygen species pathway seems to be the most important pathway because antioxidants may protect against the disturbances of both the inositol and the arachidonic pathways.…”
mentioning
confidence: 99%